DESIGN OF THE DIGITIZATION OF BRIGUNA CREDIT ARCHIVES AT PT BANK RAKYAT INDONESIA (PERSERO) TBK - Aliya Azizah; Fathiyah Nopriani (International Journal of Multidisciplinary Reseach, 2026)
The rapid development of digital technology has transformed document management in the banking sector. PT. Bank Rakyat Indonesia (Persero) Tbk, particularly in the Briguna Credit Division, still faces challenges in managing physical archives that hinder operational efficiency. This study aims to design a digital archive system for Briguna credit documentation to improve data accessibility, accuracy, and security. The research employs the Rapid Application Development (RAD) method, involving three stages: requirements planning, design, and implementation. The system integrates Optical Character Recognition (OCR) for converting scanned documents into searchable digital formats and a relational database for efficient data storage. The results demonstrate that the digitization process can reduce document retrieval time by 70% and minimize the risk of data loss. Furthermore, the proposed system supports data confidentiality, integrity, and availability, in line with OJK regulations and the Indonesian Personal Data Protection Law. This research contributes both theoretically—by applying the DeLone & McLean Information System Success Model to banking document management—and practically, by offering a structured design to support BRI’s digital transformation strategy.